The role of civil society in advancing education rights : the case of Gadra Education, Grahamstown, South Africa - Msindo, Esteri Makotore (Rhodes University, Faculty of Humanities, Department of Sociology, 2015)
This thesis has identified and analysed the role of an NGO called Gadra Education in advancing education rights to the less advantaged people of Grahamstown in South Africa. Gadra Education's role has been identified as twofold. Firstly as an educational NGO, Gadra Education's initiatives directly impact on the lives of the less economically and socially privileged learners who, due to their previous learning environment in state schools, do not achieve academic results that ensure entry into tertiary level. Secondly its role is identified in its nature as an organisation that emerged due to the deficiencies in the state schooling system. It therefore stands de facto as a critical institution for critique of the state's education system. The thesis concludes that without confronting the Department of Education or collaborating with it, Gadra Education offers a significant alternative approach which can potentially influence the state to improve the state schooling system. Its strategy of non-confrontation to the state, informal and non-corporatist is advantageous as an NGO that focuses on the actual provision of education. It focuses on instilling Ubuntu values of sharing and giving that are of critical significance in teaching and learning. The context of the thesis is located broadly within socio-economic rights and specifically on education rights. In South Africa where the state has not adequately met the educational obligations for the economically and socially less privileged citizens, the emergence of educational NGOs that focus on providing education to the poor is of vital importance. Although other NGOs that confront the state are important in pushing the state to deliver especially on school infrastructure, teacher deployment and other educational challenges, Gadra Education model ensures academic success for the learner. Lessons can be drawn from Gadra Education which can be potentially useful to state schools and other NGOs that seek to advance education rights to disadvantaged communities.
Keywords: Gadra Education (Grahamstown, -- South Africa); Right to education -- South Africa; State departments of education -- South Africa; Educational change -- South Africa; Social justice -- South Africa; Civil society -- South Africa; Social contract